Pengujian Sludge Battery Dengan Teknologi Microbial Fuel Cell Sebagai Sumber Energi Listrik Terbarukan - Ika Novia Anggraini; Afriyastuti Herawati (Universitas Bengkulu, 2018)
ABSTRACTMicrobial Fuel Cells are devices which convert chemical energy into electrical energy through catalytic reactions by microorganisms. In this study, the potential of electricity in MFC will be analyzed by using samples of sea mud, lake mud, land mud, and river mud. While the method used in this study is one series connected vessel, two vessels connected series with mud-water, two mud-mud series vessels, and the stack series method. The highest electrical conductivity produced by river mud reaches 3.63 mS/cm, while the lowest is lake mud with a conductivity value of 0.35 mS/cm. The highest electric power density produced by river mud by the two mud-mud vessel method is 46.766 mW/m2, while the lowest electrical power density in lake mud is 18.040 mW/m2. The highest electrical power is produced by river mud through a single vessel series system with a maximum power of 7.26 mW, while the lowest power is found in marine mud with a system of two mud-water vessels which is equal to 0.30 mW. The pattern of increase in voltage or current produced by the battery sludge is on average until the 7th day, then a decrease occurs until the last day of testing. The greatest potential for electrical energy is obtained by river mud using a single vessel series system with a maximum voltage of 5.38 V and lasting up to 14 days.Keyword : electric power density, microbial fuel cells, sludge battery